Late pruning modifies leaf to fruit ratio and shifts maturity period, affecting berry and wine composition in Vitis vinífera L. cv. ‘Malbec’ in Mendoza, Argentina - Bustos Morgani, Marianela; Fanzone, Martín Leandro; Perez Peña, Jorge Esteban; Sari, Santiago Eduardo; Gallo, Agustina Eugenia; Gómez Tournier, Mariana Belén; Prieto, Jorge Alejandro (Elsevier, 2024)
Higher temperatures in recent years have advanced berry ripening and harvest date, decoupling berry sugar accumulation of anthocyanins final concentration and therefore reducing wine potential color. Late pruning is proposed as a tool to modify phenology and to delay berry ripening later in the season when temperatures are lower. The aim of this work was to evaluate the effects of late pruning on berry and wine composition in cv. Malbec. During three consecutive seasons, winter pruning (WP) was compared to three late pruning treatments: plants pruned at budburst (BB), at 2–3 unfolded leaves (2–3 L), and 8 unfolded leaves (8 L). Late pruning treatments showed higher concentration of soluble solids at the same cumulated degree days (GDD) from veraison. On the other hand, while berries from 8 L presented higher levels of acidity, they presented similar value of pH. In 2018, wines from 8 L presented a higher content of phenols and total tannins; while the concentration of anthocyanins was higher in wines from 2–3 L and 8 L. In 2019, wines from 8 L plants presented higher anthocyanin content, while the rest of the parameters were similar for all treatments. Late pruning could be a useful tool to maintain or improve the phenolic composition of berries and wine, although in our conditions it was not very effective in delaying the accumulation of soluble solids for harvest. The effects of late pruning on berry maturity and composition was mediated by changes in thermal regime during maturity and leaf to fruit ratio.